PENGARUH FAKTOR – FAKTOR EKONOMI TERHADAP INFLASI DI INDONESIA PASCA-KRISIS KEUANGAN - Jechlien Melinda Reawaruw (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2017)
This study aimed to identify the influenceof Interest Rate, Money Supply, and Exchange Rate to inflationin Indonesia after Financial Crisis 2008 with quantitative approach and analyzed using OLS (Ordinary Least Square). Data Methods in this research used time series data in the period 2008:1 until 2015:2. The result of this research indicate that Interest Rate, Money Supply, and Exchange Rate simultaneously effect the inflationin Indonesia after Financial Crisis 2008. Interest Rate has a positive effect 2.755885%, Money Supply has a positive effect 1.28E-06%, and Exchange Rate have a negative effect 0.000841%. Bank Indonesia as an institution that is responsible for determining the inflatin target has a very important role and coordinate with the government in implementing fiscal policy and monetary policy appopriately.